Thermal Analyses and Responses of Bridge Deck Hydronic Snow Melting System - Junjie Feng; Guansheng Yin (Advances in Civil Engineering)
The hydronic snow melting pavement (HSMP) system is an environmentally friendly, clean, and sustainable alternative to traditional approaches for bridge deck snowmelt. The objective of this paper is to investigate the temperature field and thermal responses of HSMP by a three-dimensional finite element (3D FE) model based on the thermal-fluid coupling method. Considering the full fluid domain, the model simulates the dynamic temperature field and obtains the dynamic heat load of HSMP. Results show that the model factually simulates the decrease of fluid temperature along the pipe. The insulation of bridge deck bottom reduces heat loss, and heating demand can be lowered. Due to the ambient temperature changes, preheating is an effective approach of energy conservation and the start time of heating proposed is at 10 : 00 to 16 : 00. The flow velocity has a slight influence, and the recommended magnitude is 0.6 m/s. The shallower pipe embedded depth and the narrower pipe spacing can improve the surface temperature of HSMP and the uniformity of snowmelt process. Under ambient temperature loads, the maximum principle tensile stress of HSMP is induced at the contact interface between pipes and surrounding concrete, and the magnitude is greater than that of the conventional pavement. Under ambient temperature loads and fluid circulation, heated pipes can effectively prevent thermal shrinkage cracking and extend service life of HSMP. With increase of the pipe embedded depth and decrease of the pipe spacing, the chance of thermal shrinkage cracks decreases. For both optimum snowmelt efficiency and thermal cracking reduction, the pipe embedded depth of 7 cm and pipe spacing of 10 cm are recommended for HSMP with the inlet fluid temperature of 15°C.